Determination of organizational factors on employee attachment to work fatigue as moderation in group nurses of hospital - Sadeli, Vera Indrayani (Jurnal Konseling dan Pendidikan, 2025)
In the healthcare industry, employee engagement plays an important role in improving service quality and reducing the turnover rate of healthcare workers. Nurses who have a high level of attachment to the organization tend to be more productive, committed, and provide better services. However, various organizational factors such as interpersonal relationships, management support, transformational leadership, career development, and work environment can affect employee engagement levels. In addition, burnout is often a challenge in the industry and has the potential to moderate the relationship between organizational factors and employee engagement. This study aims to analyze the influence of organizational factors on the attachment of nurse employees in Group Hospital X with work fatigue as a moderation variable. This study uses a quantitative method with an explanatory approach. Data was collected through a questionnaire given to 222 nurses and analyzed using Moderated Regression Analysis (MRA). The results showed that only the work environment had a significant influence on employee engagement, while interpersonal relationships, management support, transformational leadership, and career development did not show a significant impact. In addition, work burnout has not been shown to moderate the relationship between organizational factors and employee engagement. Interviews with nurses revealed that although work burnout was a major challenge, intrinsic factors such as love of the profession were still the main reason they persisted. These findings provide insight for hospital management in designing more effective policies to improve the welfare of health workers.